2018
DOI: 10.1155/2018/9352608
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydraulic Gradient, Intersecting Angle, Aperture, and Fracture Length on the Nonlinearity of Fluid Flow in Smooth Intersecting Fractures: An Experimental Investigation

Abstract: This study experimentally investigated the nonlinearity of fluid flow in smooth intersecting fractures with a high Reynolds number and high hydraulic gradient. A series of fluid flow tests were conducted on one-inlet-two-outlet fracture patterns with a single intersection. During the experimental tests, the syringe pressure gradient was controlled and varied within the range of 0.20-1.80 MPa/m. Since the syringe pump used in the tests provided a stable flow rate for each hydraulic gradient, the effects of hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 46 publications
(69 reference statements)
1
2
0
Order By: Relevance
“…The present study extends the works of Li et al [32] and Wu et al [33] to study the nonlinear flow properties of a crossed fracture model consisting of two fractures with different apertures. First, three experiment models, with two fractures having different apertures, were established and flow tests were carried out.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present study extends the works of Li et al [32] and Wu et al [33] to study the nonlinear flow properties of a crossed fracture model consisting of two fractures with different apertures. First, three experiment models, with two fractures having different apertures, were established and flow tests were carried out.…”
Section: Introductionsupporting
confidence: 74%
“…Kosakowski and Berkowitz [21] depicted that the fluid flow transits from the linear regime to the nonlinear regime when Re > 10, by numerically solving the complex Navier-Stokes equations. The influences of hydraulic gradient, surface roughness, intersecting angle, and scale effect on the nonlinear flow characteristics at the intersections have been both experimentally and numerically investigated [31][32][33]. They found that the nonlinearity can be negligible when the ratio of fracture aperture to fracture length is smaller than 0.001, and the hydraulic gradient that is less than 0.001 plays a sufficiently small role on the nonlinear flow.…”
Section: Introductionmentioning
confidence: 99%
“…In the process of underground engineering, many rock hydraulics problems are related to the rock fracture pathway. Under the interaction of artificial engineering disturbance stress, in situ stress, and groundwater seepage pressure, the seepage behavior of groundwater in rock mass fractures affects the stability of fractured rock masses in engineering activities [1,2]. The safety of human engineering activities and the adverse effects of the geological environment on engineering activities are also often affected by the seepage behavior of fluids in rock fractures [3].…”
Section: Introductionmentioning
confidence: 99%
“…On account of the fact that the computational cost of applying rough texture on rock fractures is high, most earlier studies have simplified the problem by considering smooth parallel surfaces (Lemieux and Sudicky 2010, Wu et al 2018, Aghajannezhad et al 2020. The fluid flow behaviour in a single natural fracture has been thoroughly investigated in the last two decades solving the full NSE and Reynolds equation (Zou et al 2015, 2017a, Lee and Babadagli 2021.…”
Section: Introductionmentioning
confidence: 99%